Left Atrial Reservoir Function and Outcomes in Secondary Mitral Regurgitation - Stassen Jan; Namazi Farnaz; van der Bijl Pieter; van Wijngaarden Suzanne E; Kamperidis Vasileios; Marsan Nina Ajmone; Delgado Victoria; Bax Jeroen J (Elsevier Inc., 2022)
Background
Left atrial (LA) size is a marker of disease severity and is related to worse outcomes in secondary mitral regurgitation (MR). The prognostic value of LA function assessed by LA reservoir strain (LARS), however, remains unknown. The aim of this study was to investigate the prognostic implications of LARS in patients with significant secondary MR.
Methods
LARS was evaluated using speckle-tracking echocardiography in patients with more than mild (grade ≥ 2) secondary MR. The population was divided into two groups according to the median LARS value (9.8%). The primary end point was all-cause mortality.
Results
A total of 666 patients (mean age, 66 ± 11 years; 68% men) were included. On multivariable analysis, more severe MR was independently associated with more impaired LARS (LARS < 9.8%; odds ratio, 0.419; 95% CI, 0.249-0.704; P = .001). During a median follow-up period of 5 years (interquartile range, 2-10), 383 patients (58%) died. Patients with LARS < 9.8% had significantly lower survival rates at 1-, 2-, and 5-year follow-up (85%, 70%, and 45%, respectively) compared with patients with LARS ≥ 9.8% (96%, 93%, and 78%, respectively; P < .001). After multivariable adjustment (including LA volume and left ventricular global longitudinal strain), more preserved LARS (≥9.8%; hazard ratio, 0.499; 95% CI, 0.386-0.645; P < .001) was independently associated with lower all-cause mortality. LARS provided incremental prognostic value over LA volume and left ventricular global longitudinal strain.
Conclusions
LARS is independently associated with all-cause mortality in patients with significant secondary MR and has incremental prognostic value over LA volume and left ventricular global longitudinal strain. LARS may improve risk stratification of patients with secondary MR.